Analysis of Headmaster's Leadership Style in Enhancing Learning Quality at TK Mujahidin, Semarang Regency - Fauziah, Syifa; Yanto, Heri; Wasino, Wasino; Suminar, Tri (Proceedings of International Conference on Science, Education, and Technology, 2024)
This study aims to analyze the leadership style of the principal in enhancing learning quality at TK Mujahidin, Semarang Regency. The research method employed is a qualitative approach with a case study design. The study involves the principal, teachers, and school staff as respondents. The research findings indicate that the principal of TK Mujahidin, Semarang Regency, adopts a leadership style centered on collaboration and motivation. This leadership style fosters a harmonious and productive work environment within the school. The principal actively engages in the decision-making process and provides necessary support to teachers. Additionally, the principal implements effective communication strategies to ensure the involvement of all stakeholders in efforts to enhance learning quality. The study demonstrates that open and transparent communication is crucial for achieving better learning outcomes. The challenges faced by the principal include resource constraints, both financially and in terms of facilities. However, the principal has successfully overcome these obstacles by optimizing available resources and introducing innovations into the teaching and learning process. This research provides a deeper understanding of the implementation of the Merdeka Belajar Curriculum. The implications include contributions to the development of more effective, responsive, and quality early childhood education in the region.